GPR and Magnetic Surveys Above a Glacier Tunnel at SW Langjökull - Arney Ósk Guðlaugsdóttir 1999- (2023)
Located in Langjökull, Iceland, there is a man-made tunnel that has been open to the public since 2015, allowing visitors to experience a glacier from within. Over the years, this tunnel has increased in length by approximately 100 m and has also moved with the glacier for about 80 m from its initial location, showcasing the nature of glacial environments. Because this glacier is constantly moving, proper maintenance is needed on this tunnel in order for it to be safe and passable. Using magnetic and GPR surveys, the goal was to locate the tunnel and find the optimal location for a new ventilation shaft. The data from these surveys could then be used extend the lifespan of the tunnel and provide data about other objects within the glacier that might not be visible from the surface. Both surveys were done on April 15. Í Langjökli eru manngerð göng sem hafa verið í opin almenningi síðan 2015 sem veitir folki tækifæri að skoða jökul að innan. Í gegnum árin hafa göngin breyst vegna hreyfingu jökulsins. Frá því að göngin opnuðu hafa þau lengst um 100 m og hafa einnig færst um 80 m frá upphafsstað. Vegna hreyfingu jökulsins er mikilvægt að viðhalda göngunum til þess að passa upp á öryggi fólks. Notaðar voru segul og GPR mælingar til að staðsetja göngin og finna besta stað inn í göngunum til að gera nýtt loftræsti op. Gögnin úr þessari rannsókn gætu svo verið notuð til þess að lengja líftíma ganganna og gefið upplýsingar um aðra hluti sem gætu leynst undir yfirborðinu við göngin. Báðar mælingar voru framkvæmdar 15 apríl.